2020
DOI: 10.1016/j.chest.2020.08.1783
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation Improves Quadriceps Muscle Strength in Patients With Chronic Respiratory Disorders

Abstract: Skeletal muscle dysfunction is an important factor in reduced exercise capacity, impaired quality of life and higher health-care utilization in COPD. Reduced quadriceps function is associated with decreased survival, functional status, and quality of life. Relating quadriceps peak torque (Tq) to its peak electromyographic (EMG) signal (Eq) is an index that may predict fatigue during active contraction. It has not been investigated in patients with chronic respiratory disorders. The objective of this study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The findings of this study were previously reported in part in an abstract elsewhere. 34 Since the publication of the abstract, additional patients have been studied with expansion of the physiological analysis in this paper. The study was conducted between January 2019 and January 2022.…”
Section: Methodsmentioning
confidence: 99%
“…The findings of this study were previously reported in part in an abstract elsewhere. 34 Since the publication of the abstract, additional patients have been studied with expansion of the physiological analysis in this paper. The study was conducted between January 2019 and January 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Early initiation of PR can potentially minimize the effect of acute exacerbations on the skeletal muscle and prevent the deterioration of skeletal muscle to a significant extent [23], thus appearing to be an effective strategy to change the course of the disease [24]. Several other studies have demonstrated significant improvement in muscle function and quality of life [25][26][27][28][29][30], psychosocial wellbeing [31], reduction in mortality, and rate of hospitalization [32] following successful completion of PR. The benefits of PR can be further maximized by introducing supplemental nutrition [33,34].…”
Section: Pulmonary Rehabilitation: the Pressing Priority In The Management Of Copdmentioning
confidence: 99%